Novel verbal fluency scores and structural brain imaging for prediction of cognitive outcome in mild cognitive impairment. Issue 1 (15th February 2016) - Clark, David Glenn; McLaughlin, Paula M.; Woo, Ellen; Hwang, Kristy; Hurtz, Sona; Ramirez, Leslie; Eastman, Jennifer; Dukes, Reshil‐Marie; Kapur, Puneet; DeRamus, Thomas P.; Apostolova, Liana G.
Abstract: Introduction: The objective of this study was to assess the utility of novel verbal fluency scores for predicting conversion from mild cognitive impairment (MCI) to clinical Alzheimer's disease (AD). Method: Verbal fluency lists (animals, vegetables, F, A, and S) from 107 MCI patients and 51 cognitively normal controls were transcribed into electronic text files and automatically scored with traditional raw scores and five types of novel scores computed using methods from machine learning and natural language processing. Additional scores were derived from structural MRI scans: region of interest measures of hippocampal and ventricular volumes and gray matter scores derived from performing ICA on measures of cortical thickness. Over 4 years of follow‐up, 24 MCI patients converted to AD. Using conversion as the outcome variable, ensemble classifiers were constructed by training classifiers on the individual groups of scores and then entering predictions from the primary classifiers into regularized logistic regression models. Receiver operating characteristic curves were plotted, and the area under the curve (AUC) was measured for classifiers trained with five groups of available variables. Results: Classifiers trained with novel scores outperformed those trained with raw scores (AUC 0.872 vs 0.735; P  < .05 by DeLong test). Addition of structural brain measurements did not improve performance based on novel scores alone. Conclusion: The brevity and cost profile of verbal fluency tasks recommends their use for clinical decision making. The word lists generated are a rich source of information for predicting outcomes in MCI. Further work is needed to assess the utility of verbal fluency for early AD.